Wind-Driven Damage Localization on a Suspension Bridge - Marco Domaneschi; Maria Pina Limongelli; Luca Martinelli (The Baltic Journal of Road and Bridge Engineering)
The paper focuses on extending a recently proposed damage localization method, previously devised for structures subjected to a known input, to ambient vibrations induced by an unknown wind excitation. Wind induced vibrations in long-span bridges can be recorded without closing the infrastructure to traffic, providing useful data for health monitoring purposes. One major problem in damage identification of large civil structures is the scarce data recorded on damaged real structures. A detailed finite element model, able to correctly and reliably reproduce the real structure behavior under ambient excitation can be an invaluable tool, enabling the simulation of several different damage scenarios to test the performance of any monitoring system. In this work a calibrated finite element model of an existing long-span suspension bridge is used to simulate the structural response to wind actions. Several damage scenarios are simulated with different location and severity of damage to check the sensitivity of the adopted identification method. The sensitivity to the length and noise disturbances of recorded data are also investigated.